2013
DOI: 10.1039/c3ta13442c
|View full text |Cite
|
Sign up to set email alerts
|

Co3O4 nanostructures: the effect of synthesis conditions on particles size, magnetism and transport properties

Abstract: Surfactant-free Co 3 O 4 nanostructures with various particle size ranges were synthesized via the solution combustion method using cobalt nitrate solution as a cobalt precursor and urea as a combustion fuel.Control over average particles size range was achieved by tuning the reaction ignition temperature between 300 C and 800 C. X-ray diffraction (XRD) and helium gas pycnometry indicated the formation of single phase Co 3 O 4 nanoparticles with a spinel structure. Transmission electron microscopy (TEM) studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 40 publications
3
39
1
Order By: Relevance
“…A recent study on the magnetic properties of nanostructured Co 3 O 4 revealed the presence of high-spin Co 3 + (HS Co 3 + : e 3 t 2 3 ) in tetrahedral sites. [53] Generally, tetrahedral complexes are almost invariably high spin because the crystal field stabilization energy D tet is significantly smaller than D oct , and lower energy amounts are required for t 2 ! e transitions in tetrahedral fields than for e g !…”
Section: Resultsmentioning
confidence: 99%
“…A recent study on the magnetic properties of nanostructured Co 3 O 4 revealed the presence of high-spin Co 3 + (HS Co 3 + : e 3 t 2 3 ) in tetrahedral sites. [53] Generally, tetrahedral complexes are almost invariably high spin because the crystal field stabilization energy D tet is significantly smaller than D oct , and lower energy amounts are required for t 2 ! e transitions in tetrahedral fields than for e g !…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the reference value for the thermal conductivity of the nanoparticles at T = 300 K, the value j p = 16.8 W m À1 K À1 has been used according to reference [45]. Experimental thermal Fig.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…It is well known that the performances of the metal oxides are strongly depended on their morphology and structures (crystalline sizes, stacking manners, orientations, and so on), which are related to the preparation methods [6,7]. Thus, it has attracted much attention to fabricate Co 3 O 4 with various morphology and structures, for expecting the higher activity in electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%